Dengan Pendekatan Saintifik Berwawasan Ramah Anak (Studi Kasus pada Pembelajaran Lesson Study) - Nurul Kamilati (Mukaddimah: Jurnal Studi Islam, 2016)
The aim of this research was to understand the learning child friendly visionary scientific approach on lesson study at the Islamic State of Junior Secondary School of Bantul Kota. The formulation of the problem were (1) how the learning process friendly visionary scientific approach at Islamic State of Junior Secondary School of Bantul Kota?; and (2) how the response of students about the learning? This research was conducted in September - October 2014 using a qualitative approach with case study method. Data were collected through document analysis, observation, interviews, and questionnaires. The locus was at the Islamic State of Junior Secondary School of Bantul Kota.The conclusion of this study was learning lesson study with a scientific approach has shown child-friendly learning as well as (1) The learning process of lesson study at the locus was appropriate with learning child-friendly indicators and (2) the response of students to their learning was they had learning child friendly. The suggestion for the next lesson study or learning in otherplaces was learning child friendly visionary scientific approach. The recomendation for Religious Training Center was to develop a child-friendly learning through activity-based lesson study continously. It should prepare The Curricula of Lesson Study Based Learning Child friendly.